Uso de microondas na síntese de 3-alquil(aril)-5-hidróxi-5-triclorometil-4,5-diidro-1h-pirazol-1-carboxiamida - Muraro, Paulo Isaias Rossato (2005)
A series of 3-alkyl and 3-aryl-5-hydroxy-5-trichloromethyl-4,5-dihydro-1Hpirazoles-1-carboxiamide that possess biological activity they were synthesized, in good yeld, through the cyclocondensation, in microwaves, of 4-alcoxi-1,1,1-trihalometyl-3alquen-2-onas with semicarbazyde chloride using MeOH/H2O as solvent. The advantage obtained with the use of irradiation of microwaves in relation to the classic methodology it is the decrease of the time reacional and revenue increase as it will be demonstrated.